HOW COULD THINKING ABOUT OTHER RELIGIONS BE ENRICHED BY THE PRIESTHOOD OF CHRIST? - O’Collins, Gerald (Asian Horizons, 2019)
Since the Second Vatican Council (1962–65), much has been written on the theology of religions and, in particular, on the question of salvation reaching those who follow other faiths. This article starts from Vatican II’s Constitution on the Sacred Liturgy, Sacrosanctum Concilium, and the Letter to the Hebrews, and presents the priesthood of Christ as a high[1]priestly intercession that mediates salvation to all human beings and establishes a new covenant for all people. The article also draws on the letters of St Paul and the Gospel of John to emphasize the high[1]priesthood of Christ and propose a Christology of religions, which is developed at full length in the author’s A Christology of Religions (Maryknoll, NY: Orbis Books, 2018).